Estudios evolutivos del desarrollo en tallos fósiles de Corystospermaceae (Corystospermales, Spermatopsida) - Bodnar, Josefina (2012)
Evolutionary developmental studies in fossil stems of Corystospermaceae. A methodological critera to study the development of permineralized stems is proposed, which is applied in the analysis of the evodevo patterns of Corystospermaceae axes, the most important Mesozoic seed fern family in gondwanic Triassic paleofloras. This group accounts for an excellent case study because their stems are preserved permineralized, showing cellular and histological details, and it is possible to examine their whole ontogeny in a single individual since the cells of the secondary xylem and phloem are produced in successive layers retaining permanently their position. In the ontogenetic studies of pteridosperms, regulating mechanisms of development must be discerned comparing with ontogenies of comparable living plants. This extrapolation is possible since it is known that regulating processes of secondary growth are homologous in all lygnophytes. Most of corystosperm axes present a dissected secondary vascular cylinder, and tissues with unusual development and position, which is caused by four classes of cambial deviations: 1-differential activity throughout the stem circumference; 2-remnant activity; 3-inverse or centripetal cambium; and 4-successive inverse and/or normal cambia (poyxyly). The origin of these cambium deviations is intimately linked to heterotopic events, including neoheterotopy and homeosis. By comparison with living plant studies, it is theorized that homeotic genes implied with these events could be those related to the beginning of cambial activity, cell differentiation, and vascular bundle arrangement.